2008
DOI: 10.1097/tp.0b013e318187748f
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Pediatric Liver Transplantation: A Long-Term Follow-Up Study

Abstract: Renal function is a major concern long after OLT in children. Renal dysfunction post-OLT may be reduced by optimal control of arterial hypertension, immunosuppression protocols adapted to primary liver disease, and calcineurin inhibitor sparing regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 26 publications
5
66
0
3
Order By: Relevance
“…While an increased risk of kidney dysfunction with cyclosporine has frequently been hypothesized, a true difference between cyclosporine and tacrolimus may be missed in single center studies, in which the majority of patients receive the same calcineurin inhibitor based on center standard. In addition, center standards tend to change over time, such that use of cyclosporine immunosuppression frequently correlates with transplant era, further complicating any relationship between immunosuppressive agent and clinical outcome (22,25,28). Our results are in keeping with the multicenter study by Ojo and colleagues, in which cyclosporine immunosuppression was found to be a risk factor for chronic kidney disease in LT patients specifically (10).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While an increased risk of kidney dysfunction with cyclosporine has frequently been hypothesized, a true difference between cyclosporine and tacrolimus may be missed in single center studies, in which the majority of patients receive the same calcineurin inhibitor based on center standard. In addition, center standards tend to change over time, such that use of cyclosporine immunosuppression frequently correlates with transplant era, further complicating any relationship between immunosuppressive agent and clinical outcome (22,25,28). Our results are in keeping with the multicenter study by Ojo and colleagues, in which cyclosporine immunosuppression was found to be a risk factor for chronic kidney disease in LT patients specifically (10).…”
Section: Discussionsupporting
confidence: 81%
“…Alagille syndrome in particular emerges as a likely candidate due to the association of the syndrome with both growth retardation and structural and/or functional kidney disease (44). In an attempt to clarify the relationship between kidney function and diagnosis, we re-analyzed the data stratifying diagnosis by known risk of primary kidney involvement (high risk group: Alagille syndrome, alpha-1-antitrypsin deficiency, Wilson's disease, glycogen storage disease, tyrosinemia and congenital hepatic fibrosis), as did Harambat et al in their 2008 paper (28). Interestingly, using this classification primary diagnosis was not significant in the univariate analysis (p-value 0.2888).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who have experienced significant renal injury prior to liver transplantation are often left with little renal reserve to tolerate additional insults, such as ischemia-reperfusion damage. In a multivariate analysis, Harambat et al found children undergoing liver transplantation with a Bknown risk of primary renal involvement^had a hazard ratio of 4.47 for the development of post-transplant chronic kidney disease [28].…”
Section: Discussionmentioning
confidence: 99%
“…En Lyon efectuaron un importante estudio a largo plazo en un grupo de 69 niños trasplantados entre 1991 y 2005 y evaluaron la función renal mediante aclaramiento de inulina 40 . Hubo insuficiencia renal (aclaramiento inferior a 60 ml/min) en un 26% de los pacientes.…”
Section: Efectos De La Inmunosupresión a Largo Plazo Función Renalunclassified